Derivatives of Multivariate Bernstein Operators and Smoothness with Jacobi Weights - Jianjun Wang; Zuoxiang Peng; Shukai Duan; Jia Jing (Journal of Applied Mathematics)
Using the modulus of smoothness, directional derivatives of multivariate Bernstein operators with weights are characterized. The obtained results partly generalize the corresponding ones for multivariate Bernstein operators without weights.